PR COUNSEL FOR MA CLEAN INDOOR AIR LEGISLATION (Tufts Archival Research Center, 2007)
Marginalia; Memorandum from Susan Stuntz to Dennis Dyer regarding the Public Relations Counsel for Massachusetts Clean Indoor Air Legislation. Discusses outstanding issues surrounding providing support to AFL-CIO and organizational issues for the campaign. Provides suggestions for resolving issues of providing services to labor unions and payment procedure.